Introduction to mobility systems - Sulaiman, S.A. (Springer Singapore, 2019)
Mobility systems explore the movement of people, things, and ideas. This book is intended to delve into the first two. In many cases, they are referred to as the transportation systems. They are complicated issues nowadays primarily due to the drastic increase in human population and the related consequences. The differences in geographical locations, culture, socioeconomic backgrounds, politics, and many other factors make mobility systems far more complex. Â© Springer Nature Singapore Pte Ltd. 2020.